The Effects of Geometric Features of Intraluminal Thrombus on the Vessel Wall Oxygen Deprivation - Carbino, Burton; Guy, Alexander; Durka, Michael; Zakerzadeh, Rana (Frontiers in Bioengineering and Biotechnology, 2022)
The objective of this paper is to analyze the association of intraluminal thrombus (ILT) presence and morphology with oxygen transport in abdominal aortic aneurysms (AAA) and local hypoxia. The biomechanical role of the ILT layer in the evolution of the aneurysm is still not fully understood. ILT has been shown to create an inflammatory environment by reducing oxygen flux to the arterial wall and therefore decreasing its strength. It has been also hypothesized that the geometry of the ILT may further affect AAA rupture. However, no previous research has attempted to explore the effect of morphological features of ILT on oxygen distributions within the AAA, in a systematic manner. In this study, we perform a comprehensive analysis to investigate how physiologically meaningful variations in ILT geometric characteristics affect oxygen transport within an AAA. We simulate twenty-seven AAA models with variable ILT dimensions and investigate the extent to which ILT attenuates oxygen concentration in the arterial wall. Geometric variations studied include ILT thickness and ILT length, as well as the bulge diameter of the aneurysm which is related to ILT curvature. Computer simulations of coupled fluid flow-mass transport between arterial wall, ILT, and blood are solved and spatial variations of oxygen concentrations within the ILT and wall are obtained. The comparison of the results for all twenty-seven simulations supports the hypothesis that the presence of ILT in AAA correlates to significantly impaired oxygen transport to the aneurysmal wall. Mainly, we observed that ILT thickness and length are the parameters that influence decreased oxygen flow and concentration values the most, and thick thrombi exacerbate hypoxic conditions in the arterial wall, which may contribute to increased tissue degradation. Conversely, we observed that the arterial wall oxygen concentration is nearly independent of the AAA bulge diameter. This confirms that consideration of ILT size and anatomy is crucial in the analysis of AAA development.